Motivação e desempenho acadêmico entre alunos do primeiro ciclo de educação de jovens e adultos - Nepomuceno, Marcia de Souza Leite (2018)
The motivation proposition for learning has received great notoriety in several academic studies in the last years. On the other hand, there is practically no research on motivation in the population of youth and adult education students. In this perspective, this study presented three objectives: 1 - To describe the school and motivation profile of the AEJA Mackenzie School students, 2 - To verify if the history and the current school profile of these students have association with their academic performance, and 3 - To verify if the motivation for the study of EJA students is related to their academic performance. For the research, this last item is considered as a factor of greater relevance. Through an approach that follows the design of a quantitative descriptive cross-sectional study, we evaluated 87 students from Elementary Education I and II of the AEJA Mackenzie School of Youth and Adult Education. As data collection instruments, four structured questionnaires were used: (1) the Assessment Scale of Motivation to Learn for University Students (EMA-U) with the function of characterizing the type of motivation of the EJA students before learning; (2) Social Questionnaire with data on the socioeconomic profile and issues related to the previous and current school experience of the EJA students; (3) The 3rd version of the Wechsler Abbreviated Intelligence Scale (WASI III) for intelligence quotient measurement; and (4) Data provided by AEJA Mackenzie on academic performance and avoidance. After analyzing the results, in characterizing the students profile, it was verified that the reasons for leaving school are not related to the lack of interest in the studies, since 64.4% stopped studying because they needed to work. As to the reasons for resuming studies at the EJA, there was a predominance of the category "desire to learn to read and write", with the result 47.1% of respondents. Two aspects evaluated regarding childhood school history were associated with the better current performance of adults in EJA: those who learned to read and write as a child (CR: 3.57, 95% CI: 1.47-8, 68) and those whose parents encouraged studies during childhood (CR: 3.24; 95% CI: 1.33 -7.90). The main hypothesis of the study was not proven, since there were no statistically significant associations between motivation as a consequence of academic performance (computed in 2016, p = 0.79) nor as a predictor of performance (analyzed in 2017, p = 0.37 ). Some limitations arose in the accomplishment of this research, which could have compromised the results, namely: the small sample size, short procedure time in the collection and application of the instruments and the use of the EMA-U Scale for the first time with the public of the EJA. It is hoped that this material inspires further research with the recommendation that new research be conducted on larger samples to measure results for a better understanding of the motivation effects on academic performance in the EJA